Monofunctional DNA-platinum(II) adducts block frequently DNA polymerases. - Holler, E (1992)
The question of whether monofunctional DNA platinum(II) adducts block synthesis of DNA by purified DNA polymerases of different types and origin has been investigated by comparing the time dependence of synthesis arrest and of DNA adduct formation. Activated salmon testis DNA is used as a suitable substrate for DNA synthesis allowing to probe inhibition by platinum(II) monoadducts for the variety of inherent template-primers. Reaction amplitudes are related to defined mixtures of dichloro and chloroaqua platinum(II) complexes. It is found that (i) all investigated DNA polymerases seem arrested (100% efficiency) at bifunctional DNA adducts. (ii) human DNA polymerase beta bypasses most of the monofunctional lesions of the three platinum(II) complexes investigated. (iii) Klenow fragment is blocked by monoadducts with increasing efficiency in the order cis-diamminechloroaquaplatinum(II) (0%) less than meso-[1,2-bis(2,6- dichloro-4-hydroxyphenyl)ethylenediamine] chloroaquaplatinum(II) (50%) less than trans-diamminechloro-aquaplatinum(II) (75%). (iv) Escherichia coli DNA polymerase I, Thermus aquaticus DNA polymerase, Physarum polycephalum DNA polymerase alpha, and calf thymus DNA polymerase alpha appear to be arrested by monoadducts. According to these examples, blocking efficiencies depend on the cis/trans-stereogeometry of fixation of the carrier ligands at platinum(II) residues, on the size/chemical nature of the platin(II) carrier ligand and on the type/origin of DNA polymerase.